THE MECHANISM OF USING EDUCATIONAL PROJECTS IN THE DEVELOPMENT OF COGNITIVE ACTIVITY OF FUTURE TEACHERS BASED ON AN INNOVATIVE APPROACH - Yuldasheva Malohat Erkinovna (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, based on an innovative approach, comments are made on the mechanism of using educational projects in the development of cognitive activity of future teachers and on the significance of educational forms in the development of cognitive activity of students.